Kepuasan Kerja Dengan Komitmen Organisasi Pada Karyawan - Indah Sofi Ayu; Yunita Yunita (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This research aims to explore the relationship between job satisfaction and organizational commitment to gain a deeper understanding to determine which job satisfaction can influence employee commitment to the organization and how this impacts employee commitment to the organization. The problem focuses on job satisfaction which can influence an employee's work discipline in a better direction, this is because the employee has achieved psychological satisfaction which gives rise to a positive attitude from the employee to approach this problem, a theoretical reference from Baron & Greenberg (in Aisyah, 2015) that commitment means a strong acceptance within the individual of the company's goals and values, so that the individual will try and work and have a strong desire to stay with the company. This research uses a literacy review method using Systematic Literature Review (SLR). The results of the literature review show that there is a significant positive relationship between job satisfaction and organizational commitment. Employees who are satisfied with their jobs tend to have a higher commitment to their organizations, which in turn can improve organizational performance and stability. These findings emphasize the importance of companies developing strategies that increase job satisfaction to strengthen organizational commitment.